Pelayanan Pastoral yang Efektif dan Efisien (Refleksi dari Perspektif Pelayanan Publik) - Keristian Dahurandi (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
Pastoral service is a shepherding activity performed in Catholic Church for obtaining eschatological salvation. The eschatological salvation begins in this world and will be completed in when we face to face meet God. To gain such a salvation, an effective and efficient pastoral service is needed. An effective pastoral service is characterized by ability of facilitating the people of God to have a real, concrete and measured salvation in the world and will be completed. An efficient pastoral service, however, is a rationality of input resource of the salvation reached in pastoral activities. The rationality of such a service is measured by valuating gained profit as a standard of effective service. To reach this end, pastoral service of the Church as an institution, at least, should improve some principles such as productivity, service quality, responsivity, responsibility, accountability, effectivity, efficiency, reallybility, trustworthy and justice. In addition, pastoral service needs a shift of paradigm to be more “listening” than “telling”, “serving” rather than “controlling” in order to avoid the “comfort zone”. This also requires management principles, among others: catalytic pastoral, ecclesiastical pastoral, competitive pastoral, mission-zeal pastoral, results-oriented pastoral, faith-oriented (Church), producing-oriented pastoral rather than spending, anticipatory pastoral; bottom up pastoral, a “market” system for pastoral competitive.